Tortoise Plastron and Deer Antler Gelatin Prevents Against Neuronal Mitochondrial Dysfunction In Vitro: Implication for a Potential Therapy of Alzheimer’s Disease - Cheng, Dan; Yang, Xin-Jing; Zhang, Lu; Qin, Zong-Shi; Li, Wen-Qi; Xu, Hai-Chun; Zhang, Zhang-Jin (Frontiers in Pharmacology, 2021)
Mitochondrial dysfunction with oxidative damage plays the fundamental roles in the pathogenesis of Alzheimer’s disease. In traditional Chinese medicine (TCM) practice, animal tissue-derived gelatins are often used as nootropic agents to treat cognitive deterioration and senile dementia. Tortoise plastron gelatin (TPG) and dear antler gelatin (DAG) are the two most commonly used gelatins for this purpose. This study sought to examine the effects of the two gelatins in preventing neuronal mitochondria from oxidative damage. PC12 cells, a cell line derived from rat pheochromocytoma, exposed to the neurotoxin Aβ25-35 served as an in vitro model of Alzheimer’s disease. The cells were separately pre-treated with TPG and DAG at various concentrations ranging from 6.26 µg/ml to 200 µg/ml, followed by co-incubation with 20 μM Aβ25-35 for different duration. Cell viability, mitochondrial membrane potential (MMP) and ultrastructure, intracellular ATP, reactive oxygen species (ROS) and calcium (Ca2+) level, the expression of mitochondrial dynamic proteins and biomarkers of apoptosis were measured. Pretreatment with TPG and DAG reversed the Aβ-induced reduction of cell viability in a dose-dependent manner. Both TPG and DAG significantly increased MMP and ATP, alleviated the accumulation of damaged mitochondrial fragments, and normalized the aberrant expression of multiple mitochondrial dynamic proteins of the Aβ-exposed cells. Both gelatins also suppressed intracellular ROS overproduction and Ca2+ overload, overexpression of cytochrome c and pro-apoptosis biomarkers induced by the Aβ exposure. These results suggest that TPG and DAG may have the anti-dementia potential by preventing neuronal mitochondria from oxidative damage.